A Systematic Review of Kaizen Approach in Industries - Barata Sutrisno; Erry Rimawan; Tosty Maylangi Sitorus (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2022)
Today industries are currently entering the best possibility to action on rapidly changing customer needs, desires and experiences. In the environment of industries, as well as cultural competitiveness and improving market share in the global narrowing market saturation is a big concern, the concept of continuous improvement of manufacturing processes strive to the best experiences to customers has become necessary. Market competition and continuously increasing levels of service and needs for customer satisfaction have proven to be the ultimate driver of an organization's key performance continuous improvement. Adaptable Kaizen refers to sustainable continuous improvement in performance delivery, cost, and quality to a satisfied customer. This paper contribution to define research variable domination in various tools used in Kaizen concept and research variable of Kaizen dominated by VSM and Continuous Improvement with the same percentage number 21%, then Lean 18%, TPM 10%, 5S 8%, PDCA 4%, in this calculation one research paper can use more than one tools of Kaizen.